MEMBANGUN KEUNGGULAN BERSAING UNTUK MENINGKATKAN KINERJA BISNIS PADA INDUSTRI KECIL MENEGAH TENUNG IKAT DI TROSO, JEPARA - Tiorina M, Mona; Sugiarto, Johanes (JURNAL BISNIS STRATEGI, 2016)
This study aimed to examine the effect of entrepreneurial orientation, market orientation, and competitive advantage on business performance. The issue discussed in this research was how the entrepreneurial orientation and market orientation can affect the competitive advantage to improve business performance.Model refinement using outlier evaluation and composite indicators was conducted in this study, so that the research results found that interpret the condition of Small and Medium Industries Tenun Ikat Troso Jepara.. The samples obtained were the owner and manager of Tenun Ikat business in Troso, Jepara, amount to 125 respondents. The data can be used from 125 respondent are 115 respondent. This research used Structural Equation Modeling (SEM) which was run by an AMOS 20,0 to analyze the data.The sampling technique used in this study is purposive sampling. The result of SEM data processing already found the goodness of fit follows, the value of chi square= 78,577; df : 72; p : 5%; probability = 0,278; GFI = 0.914; AGFI = 0,875; TLI = 0,989; CFI= 0,991; CMIN/DF = 1,091; RMSEA = 0.028. Thus, it can be said that this model is appropriate used.The empirical findings in this study showed that entrepreneurial orientation has significant positive affect on competitive advantage, market orientation has negative affect on competitive advantage, competitive advantage has significant positive affect on business performance, entrepreneurial orientation has negative affect on business performance, and market orientation has positive affect but not significant to business performance.